P169 A CASE OF SUCCESSFUL INDUCTION OF REMISSION IN MODERATE-TO-SEVERE STEROID REFRACTORY ULCERATIVE COLITIS USING HERBAL THERAPY. (18th January 2018) - Lee, Alice; Mandaliya, Rohan; Mattar, Mark C
Abstract: Introduction: The use of Complementary and Alternative Medicine (CAM) is prevalent in patients with ulcerative colitis (UC). Most randomized clinical trials (RCT) of herbal supplements in UC studied inactive or mild-to-moderate UC, and they were small studies. We present a case of moderate-to-severe UC that reached endoscopic and clinical remission with patient-driven regimen of herbal supplements. Case Description: A 38 year-old male with a 3-year history of UC presented with weight loss, frequent bowel movements and tenesmus despite mesalamine and prednisone. His colonoscopy showed inflammation of sigmoid colon and rectum, consistent with worsening moderate-to-severe UC. (Fig. 1) The subsequent plan was escalation of therapy to anti-TNF agent. However, he tested positive for tuberculosis (TB) screen and started latent TB treatment. During this time, he visited a CAM provider. He never initiated escalated therapy and was able to control his symptoms. When he returned for UC surveillance at age 41, off routine medications for 3 years, his colonoscopy showed normal mucosa. (Fig. 1) He achieved clinical, endoscopic and histologic remission with oral regimen of: wheatgrass 2.5g, turmeric 475mg and probiotics every morning; twice daily of aloe vera juice 2-ounces and fish oil 1.6g; and filtered vegetable and fruit juice containing ginger. He never required steroids since starting his herbal regimen. The predicted mechanism and literature review of supplements are summarized in Table 1. Discussion: The evidence for most herbal supplements in UC is limited. Some have been studied in RCTs, but with small and heterogeneous designs. Our patient achieved successful deep remission from moderate-to-severe UC proctosigmoiditis solely with his CAM regimen. Under close surveillance, it may be reasonable to consider their use in patients with active UC. We should be cautioned, however, that they are non-regulated products, with uncertain purity and side effects.